Evaluation of yield traits in some primitive wheat genotypes to ensure sustainability of wheat production - Maysoun Saleh; Fariza. Alsarhan (Innovations in Agriculture)
Study was conducted at Al-Raqqa Research Centre in The General Commission for Scientific Agricultural Research in Syria during the growing seasons 2011/2012. Eight primitive wheat genotypes and two local cultivated varieties were planted in Randomized Complete Block Design in three replications, yield components (number of fertile tillers, number and weight of grains per spike and weight of thousand grain) were studied. Results showed that the genotype Persian 64 was significantly superior in three traits of yield components (number of fertile tillers, number and weight of grains per spike) comparing to the check sham5, and also the genotype Polish 194 was significantly superior in weight of thousand grain comparing to both checks sham3 and sham5 (53.12, 40.80, 40.02) g respectively with an increase rate 30.20% and 32.73% comparing to both checks sham3 and sham5 respectively. It is recommended to use the superior genotypes in breeding programs to ensure the sustainability of wheat production.